Abnormal presentation of haemorrhagic adrenal cyst. Issue 5 (26th May 2021) - Aboueldahab, Kheloud; Yikona, Joseph; Hasan, Nayeem
Abstract : An 81-year-old patient presented with fever and lethargy for 3 weeks. There were no other signs or symptoms of infection. Detailed history revealed a fall onto his right flank, prior to the start of fever. All microbiological, autoimmune and oncological investigations were negative. CT scan of chest, abdomen and pelvis showed haemorrhage in a previously diagnosed simple adrenal cyst. The cyst was non-functioning. The patient continued to spike fever in the following 4 weeks, otherwise remained stable. The patient was managed conservatively as haemoglobin level was stable. Repeated scan showed signs of improvement. He was discharged after 5 weeks. He remained afebrile and asymptomatic at the planned endocrinology outpatient follow-up after 8 weeks.